Antiplasmodial activity study of angiotensin II via Ala scan analogs. (9th May 2014) - Silva, Adriana Farias; Bastos, Erick Leite; Torres, Marcelo Der Torossian; Costa‐da‐Silva, André Luis; Ioshino, Rafaella Sayuri; Capurro, Margareth Lara; Alves, Flávio Lopes; Miranda, Antonio; de Freitas Fischer Vieira, Renata; Oliveira, Vani Xavier
<x xml:space="preserve">Abstract</x> Angiotensin II (AII) as well as analog peptides shows antimalarial activity against Plasmodium gallinaceum and Plasmodium falciparum, but the exact mechanism of action is still unknown. This work presents the solid‐phase synthesis and characterization of eight peptides corresponding to the alanine scanning series of AII plus the amide‐capped derivative and the evaluation of the antiplasmodial activity of these peptides against mature P. gallinaceum sporozoites. The Ala screening data indicates that the replacement of either the Ile5 or the His6 residues causes minor effects on the in vitro antiplasmodial activity compared with AII, i.e. AII (88%), [Ala6]‐AII (79%), and [Ala5]‐AII (75%). Analogs [Ala3]‐AII, [Ala1]‐AII, and AII‐NH2 showed antiplasmodial activity around 65%, whereas the activity of the [Ala8]‐AII, [Ala7]‐AII, [Ala4]‐AII, and [Ala2]‐AII analogs is lower than 45%. Circular dichroism data suggest that AII and the most active analogs adopt a β‐fold conformation in different solutions. All AII analogs, except [Ala4]‐AII and [Ala8]‐AII, show contractile responses and interact with the AT1 receptor, [Ala5]‐AII and [Ala6]‐AII. In conclusion, this approach is helpful to understand the contribution of each amino acid residue to the bioactivity of AII, opening new perspectives toward the design of new sporozoiticidal compounds. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.